Analisis Tegangan Tembus Arus Bolak Balik Pada Minyak Nyamplung (Colophyllum Inophyllum) Sebagai Alternatif Isolasi Cair - Luchman Wira Admaja; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study is looking for the ratio of breakdown voltage between mineral oil and Colophyllum Inophyllum oil as an alternative of liquid insulation. The test of oil uses a yellowish half-ball electrode, yellowish ball electrode, and aluminium balls electrode. The value of oil breakdown voltage Colophyllum Inophyllum is higher than mineral oil. By test result, breakdown voltage that a yellowish half ball electrode is higher than by ball electrode and aluminium ball electrode. This study also varies electrode, gap space, and water level on Colophyllum Inophyllum oil to determine the effect of breakdown voltage. Less water level in oiled higher of value of breakdwon voltage is higher. To be alternative liquid insulation must fulfill with the standared spesifications liquid insulation with Colophyllum Inophyllum oil has been met some certain criterias such as breakdown voltage, flash point, viscocity, and water content. On the other side spesifications of density and pour point do not meet yet the standared spesifications of liquid insulation.Keywords: Liquid insulation,breakdown voltage, Colophyllum Inophyllum oil